-1/n-93=-7

Simple and best practice solution for -1/n-93=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/n-93=-7 equation:



-1/n-93=-7
We move all terms to the left:
-1/n-93-(-7)=0
Domain of the equation: n!=0
n∈R
We add all the numbers together, and all the variables
-1/n-86=0
We multiply all the terms by the denominator
-86*n-1=0
We add all the numbers together, and all the variables
-86n-1=0
We move all terms containing n to the left, all other terms to the right
-86n=1
n=1/-86
n=-1/86

See similar equations:

| -67-j/5=74 | | 75+f/8=83 | | 2(q-10)=18 | | c+7/5=5 | | 29+p/10=36 | | -2(s-98)=10 | | m+18/7=4 | | m+18/17=4 | | -3(m+15)=-15 | | -4(1.5x-5)+4x=2 | | 4=-4w+2(w-7) | | 15x-6=10x+6 | | 2(3x+2)+1=29 | | 6u-62=4u | | 3y+54=12y | | 18=3/4(36.4-n | | 63=15w-8w | | 21+2f=23 | | 5.31=p9. | | (2x-8)(2x-4)=0 | | 1/3y+8=4 | | 3.4(-3x-11)=-49.3(3x-16) | | 2x+100=70 | | 6m+1.25=6.9 | | -2x+24=4x+6 | | -20=m/14 | | y=22/11 | | 6-4(x+1)=2(3x+2) | | x+2x+x+2x=12 | | (18-x)60=(x-3)40 | | e-(-3)=-19 | | 1/(110000/(1+(1-23)*0.044225)/3600-(x)=0 |

Equations solver categories